The aspects of possibility to apply alternative fuel injection systems - Naginevičius, Vytenis; Lendraitis, Vitas (Transport, 2004)
In the report the short review of the constructional peculiarities of electro‐magnetic fuel injectors is discussed. The alternative mechanism constructions operated by vibrations and their operation principles are described. The mathematical model of the system is created. The motion existence conditions as well as stable and unstable moving element positions in the system are analyzed. The vibration excitation schemes in the standing wave mode and changing the tube fastening modes in the system are reviewed. The perspectives of new construction development and application are defined.First Published Online: 27 Oct 2010